Multimodal Repair of Spinal Cord Injury With Mesenchymal Stem Cells - Yuan-huan Ma; Qing-yue Liang; Ying Ding; Inbo Han; Xiang Zeng (Neurospine, 2022)
Spinal cord injury (SCI) is a result of a devastating injury to the central nervous system. Currently, there is no effective treatment available for these patients. The possible use of mesenchymal stem cell (MSC)-based treatment for SCI has been the focus of extensive investigations and is increasingly moving from the bench to bedside. Both experimental observations and clinical studies have shown the safety and efficacy of MSCs in managing SCI. However, the exact mechanism by which MSCs contribute to the repair of the injured spinal cord remains to be elucidated. In this review, we aim to summarize current research findings about the role of MSCs in improving complex pathology after SCI. MSCs exert a multimodal repair mechanism targeting multiple events in the secondary injury cascade. Our recent results showing the perineurium-like differentiation of surviving MSCs in the injured spinal cord may further the understanding of the fate of transplanted MSCs. These findings provide fundamental support for the clinical use of MSCs in SCI patients. Under experimental conditions, combining novel physical, chemical, and biological approaches led to significant improvements in the therapeutic efficacy of MSCs. These findings hold promise for the future of cell-based clinical treatment of SCI.